2021
DOI: 10.1111/pedi.13271
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized lipid‐associated protein damage in children and adolescents with type 1 diabetes mellitus: New diagnostic/prognostic clinical markers

Abstract: Background: Type 1 diabetes mellitus (DM1), a chronic metabolic disorder of autoimmune origin, has been associated with oxidative stress (OS), which plays a central role in the onset, progression, and long-term complications of DM1. The markers of OS lipid peroxidation products, lipid hydroperoxides (LOOH), and also malondialdehyde (MDA) and thiobarbituric reactive substances (TBARS) that oxidatively modify proteins (Pr) (i.e., PrMDA and PrTBARS, respectively), have been associated with DM2, DM1, diabetic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This is of particular concern, knowing that T2DM has a more aggressive course in adolescents than in adults and that progression to insulin dependence due to deterioration of β cell function is rapid 34 . The age at presentation of T1DM was younger compared to previous years in a study from Spain 35 , whereas no statistical difference was found in the age at presentation in a study from Greece 36 . Increased severity and frequency of DKA at diagnosis has also been documented, hypothetically due to delayed care-seeking or, hypothetically, due to SARS-CoV-2 aggressiveness 36 37 .…”
Section: Endocrine Diseasementioning
confidence: 66%
“…This is of particular concern, knowing that T2DM has a more aggressive course in adolescents than in adults and that progression to insulin dependence due to deterioration of β cell function is rapid 34 . The age at presentation of T1DM was younger compared to previous years in a study from Spain 35 , whereas no statistical difference was found in the age at presentation in a study from Greece 36 . Increased severity and frequency of DKA at diagnosis has also been documented, hypothetically due to delayed care-seeking or, hypothetically, due to SARS-CoV-2 aggressiveness 36 37 .…”
Section: Endocrine Diseasementioning
confidence: 66%
“…From another point of view, in the present study, there were indicators of oxidative stress such as elevated ROS generation and AGEs deposition in the tissue of the GDM mothers. Kostopoulou et al showed that oxidative stress leads to the development of DM and its complications (25). Cristian E. indicated that GDM exposes the placenta to a hypoxic environment that would disturb vascular function on account of persistently increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse mothers and their embryos were sampled for their livers which were homogenized and further processed for O 2 •− determination, by a protocol by our lab described elsewhere [ 41 ]. PrMDA and PrTBARS quantification: Liver/embryo total proteins were isolated during O 2 •− determination protocol execution, solubilized in ~50 µL 0.05 M NaOH, ~5 μL of which was ~20×-diluted with ddH2O and its protein content was quantified (as bovine serum albumin, BSA, equivalents) by an ultra-sensitive sensitive assay also developed by our lab [ 42 , 43 ]. OS marker values are expressed per mg BSA equivalents.…”
Section: Methodsmentioning
confidence: 99%